Aberrant Motility in Unaffected Small Bowel is Linked to Inflammatory Burden and Patient Symptoms in Crohn's Disease. Issue 2 (February 2016) - Menys, Alex; Makanyanga, Jesica; Plumb, Andrew; Bhatnagar, Gauraang; Atkinson, David; Emmanuel, Anton; Taylor, Stuart A.
Abstract : Background: Inflammation-related enteric dysmotility has been postulated as a cause for abdominal symptoms in Crohn's disease (CD). We investigated the relationship between magnetic resonance imaging–quantified small bowel (SB) motility, inflammatory activity, and patient symptom burden. Methods: The Harvey–Bradshaw index (HBI) and fecal calprotectin were prospectively measured in 53 patients with CD (median age, 35; range, 18–78 years) the day before magnetic resonance enterography, which included a dynamic (cine), breath-hold motility sequence, repeated to encompass the whole SB volume. A validated registration-based motility quantitation technique produced motility maps, and regions of interest were drawn to include all morphologically normal SB (i.e., excluding diseased bowel). Global SB motility was correlated with calprotectin, HBI, and symptom components (well-being, pain, and diarrhea). Adjustment for age, sex, smoking, and surgical history was made using multivariate linear regression. Results: Median calprotectin was 336 (range, 0–1280). Median HBI, motility mean, and motility variance were 3 (range, 0–16), 0.33 (0.18–0.51), and 0.01 (0.0014–0.034), respectively. Motility variance was significantly negatively correlated with calprotectin (rho = −0.33, P = 0.015), total HBI (rho = −0.45, P < 0.001), well-being (rho = −0.4, P = 0.003), pain (rho = −0.27, P = 0.05), and diarrhea (rho = −0.4, P = 0.0025). The associations remained highly significant after adjusting for covariates. There was no association between mean motility and calprotectin or HBI ( P > 0.05). Conclusions: Reduced motility variance in morphologically normal SB is associated with patient symptoms and fecal calprotectin levels, supporting the hypothesis that inflammation-related enteric dysmotility may explain refractory abdominal symptoms in CD. Abstract : Article first Published online 26 October 2015